Mathematical Connections of Students Viewed from Adversity Quotient in Problem-Based Learning Using Math City Map - Supono, Lilik; Agoestanto, Arief; Wijayanti, Kristina (AlphaMath : Journal of Mathematics Education, 2024)
The connection between mathematics and adversity quotient (AQ) has an important role in a person's ability to make decisions to solve problems in life. One of the efforts to improve it is through the application of technology in learning. The Math-City Map (MCM)-assisted Problem-based learning (PBL) model is one of the learnings that utilizes technology combining the PBL model and MCM-assisted learning. This study aims to (1) the quality of learning with a problem-based learning model using a math city map on mathematical connection ability (KKM, (2) test the effect of AQ on students' mathematical connection ability in MCM-assisted PBL learning. This research is a mixed method research with an explanatory sequential design with a quantitative portion greater than qualitative. The population of this study was grade VII students of SMPN 2 Ambarawa. Qualitative data was taken based on students' AQ, namely the climber, camper, and quitter categories. Quantitative data analysis techniques with parametric statistics such as mean tests, classical due diligence, and regression tests. Qualitative data analysis techniques use data reduction, presentation, and conclusions. The results showed that (1) MCM-assisted PBL learning was effective in improving students' mathematical connections (2) there was an influence of AQ on students' mathematical connection abilities in MCM-assisted PBL learning